TEACHING THE BASIC TECHNICAL ACTIONS OF FOOTBALL - Djurayev Elyorjon Madaminovich (Bright Mind Publishing, 2026)
This article examines the process of teaching the basic technical actions of football and ways to improve its effectiveness. The study analyzes a training methodology aimed at developing key technical elements of football players, such as ball control, passing, receiving, and shooting at goal. During the training process, changes in the level of technical preparedness of football players were studied through the use of a specially selected set of exercises, based on experimental and control groups. The research results indicate a significant improvement in the accuracy and speed of performing technical actions. The obtained conclusions have practical significance for improving technical training in football practice and are recommended for coaches and physical education specialists.
Keywords: Football, technical training, technical actions, football training, pedagogical approach, sports methodology, sports pedagogy.